Evaluation of FE-software for mechanical analysis of composite materials - Karlsson, Henrik (2005)
This thesis is the final part of a master degree in mechanical engineering at Luleå University of Technology. The thesis has been performed during autumn 2004 at Volvo Aero Corporation in Trollhättan. The objective is to evaluate and recommend a Finite Element software and analysis process for mechanical analysis in composite materials. Areas of investigation are material properties, preprocessors, solvers and postprocessors. The material properties must be calculated with consideration to the local fiber orientation and thickness of the composite. This can be made inside or outside the preprocessor depending on the software capabilities. In the preprocessing phase is the material oriented towards the geometry. The solver is the number crunching part of the analysis with almost no interference by man but it is important to have knowledge about the solvers capabilities. In the post processing phase are the results examined and this requires special care for composites due to their failure behavior. The recommended software to use is the preprocessor Patran Laminate Modeler together with the solver Nastran. The recommended working method can be described as a zone based design method where the geometry is divided in zones. These zone divisions are depending on the local loading state, material thicknesses, ply drop offs and geometric location. The working method have been tested and evaluated and have shown to serve satisfactory. Also the FE-software trustworthiness has been tested by comparing a 3-points bending of a wing profile performed at Sicomp with a similar model in the FE-software. FE-analysis in composite materials is more time consuming than for isotropic materials. The software of today has lack of capabilities for the use of solid elements together with composite materials. Validerat; 20101217 (root)